Determining the optimal load for resisted sprint training with sled towing - Alcaraz, P. E.; Palao, J. M.; Elvira, J. L. L. (The Journal of Strength and Conditioning Research, 2009)
An excessive load in resisted sprint training can produce changes in running patterns. Therefore, load control is essential to ensure the specificity of these training methods. The most common way to control it is through the percentage of velocity lost in relation to maximum velocity. The present paper describes a study that aimed to establish the load for sprint training with sled towing. The study developed a regression equation for calculating the load in the maximum velocity phase. The calculation was done with 26 athletes from the Spanish and French national levels on a synthetic track surface and with spikes. The regression equation obtained was % body mass = (-0.8674 × % velocity) + 87.99. The equation, although specific for type of surface used and sled towing characteristics, is useful in establishing the optimal load for acceleration and maximum velocity training with sled towing.